212k views
3 votes
Simplify 3(tan ^2 0 - sec^2?0)

Simplify 3(tan ^2 0 - sec^2?0)-example-1
User Bacardi
by
7.8k points

2 Answers

5 votes

Answer:

Explanation:

answer is -3 because tan^2 theta-sec^2 theta means -1 and when u multiply -1 and 3 u will get -3.

User Thornhale
by
7.4k points
6 votes

A trigonometric expression is given to us and we need to simplify it and find out the value.

Given Expression :-


\sf\implies 3(tan^2\theta - sec^2\theta )

Using Identity :-


\sf\implies sec^2\theta - tan^2\theta =1

So that ,


\sf\implies tan^2\theta -sec^2\theta = -1

Substitute the value :-


\sf\implies 3(tan^2\theta - sec^2\theta ) \\\\\sf\implies 3 *(-1) =\boxed{\red{\sf -3}}

Hence the required answer is -3 .

User Uli Schlachter
by
7.8k points